Considerations for the use and study of the Peruvian “muña” Minthostachys mollis (Benth.) Griseb and Minthostachys setosa (Briq.) Epling. - Linares Otoya, Virginia (Ethnobotany Research and Applications, 2020)
Background: The Peruvian "muña" is used in the conservation of the potato and as a medicinal plant, the pharmacological activity of its crude extracts, essential oils and their compounds such as Pulegona is corroborated by in vitro studies. Methods: In order to group the knowledge regarding the Peruvian "muña" that facilitates its use and study, an exhaustive review was carried out with the Google Scholar and Scopus search engine of the botanical and ethnopharmacological aspects and factors that may vary its chemical composition. classified the information in these subtopics. Results: The Peruvian "muña" is used by ethnopharmacology in infusions, decoctions, rubs, aromatherapy, "Walt’aska" plasters and macerates; It is used as a single component or in mixtures with other plants, the use varies according to the region. There are biotic factors that could vary its metabolism and the chemical composition of the plants used in medicine, such as the interaction with insects, and M. mollis is very heterogeneous in its genetics and morphology, other factors that influence are abiotic such as altitude and season. Conclusions: The Peruvian "muña" produces compounds of medicinal interest, but with variations in the amount that can affect its pharmacological activity, the previous knowledge of ethnopharmacology also shows different uses, this must be taken into account to improve its medicinal use and study. Keywords: Minthostachys, natural products, Peruvian "muña"